Authigenesis at the Urals Massive Sulfide Deposits: Insight from Pyrite Nodules Hosted in Ore Diagenites - Nataliya P. Safina (Minerals, 2020)
The pyrite nodules from ore diagenites of the Urals massive sulfide deposits associated with various background sedimentary rocks are studied using optical and electron microscopy and LA-ICP-MS analysis. The nodules are found in sulfide−black shale, sulfide−carbonate−hyaloclastite, and sulfide−serpentinite diagenites of the Saf’yanovskoe, Talgan, and Dergamysh deposits, respectively. The nodules consist of the core made up of early diagenetic fine-crystalline (grained) pyrite and the rim (±intermediate zone) composed of late diagenetic coarse-crystalline pyrite. The nodules are replaced by authigenic sphalerite, chalcopyrite, galena, and fahlores (Saf’yanovskoe), sphalerite, chalcopyrite and galena (Talgan), and pyrrhotite and chalcopyrite (Dergamysh). They exhibit specific accessory mineral assemblages with dominant galena and fahlores, various tellurides and Co−Ni sulfoarsenides in sulfide-black shale, sulfide−hyaloclastite−carbonate, and sulfide-serpentinite diagenites, respectively. The core of nodules is enriched in trace elements in contrast to the rim. The nodules from sulfide−black shale diagenites are enriched in most trace elements due to their effective sorption by associated organic-rich sediments. The nodules from sulfide−carbonate−hyaloclastite diagenites are rich in elements sourced from seawater, hyaloclastites and copper−zinc ore clasts. The nodules from sulfide−serpentinite diagenites are rich in Co and Ni, which are typical trace elements of ultramafic rocks and primary ores from the deposit.